Reassessing the genetic lineage tracing of lingual Lgr5+ and Lgr6+ cells in vivo - Hyun Ji Kim; Dong Woo Seo; Jaewon Shim; Jun-Seok Lee; Sang-Hyun Choi; Dong-Hoon Kim; Seok Jun Moon; Han-Sung Jung; Yong Taek Jeong (Animal Cells and Systems)
Taste buds, the neuroepithelial organs responsible for the detection of gustatory stimuli in the oral cavity, arise from stem/progenitor cells among nearby basal keratinocytes. Using genetic lineage tracing, Lgr5 and Lgr6 were suggested as the specific markers for the stem/progenitor cells of taste buds, but recent evidence implied that taste buds may arise even in the absence of these markers. Thus, we wanted to verify the genetic lineage tracing of lingual Lgr5- and Lgr6-expressing cells. Unexpectedly, we found that antibody staining revealed more diverse Lgr5-expressing cells inside and outside the taste buds of circumvallate papillae than was previously suggested. We also found that, while tamoxifen-induced genetic recombination occurred only in cells expressing the Lgr5 reporter GFP, we did not see any increase in the number of recombined daughter cells induced by consecutive injections of tamoxifen. Similarly, we found that cells expressing Lgr6, another stem/progenitor cell marker candidate and an analog of Lgr5, also do not generate recombined clones. In contrast, Lgr5-expressing cells in fungiform papillae can transform into Lgr5-negative progeny. Together, our data indicate that lingual Lgr5- and Lgr6-expressing cells exhibit diversity in their capacity to transform into Lgr5- and Lgr6-negative cells, depending on their location. Our results complement previous findings that did not distinguish this diversity.